2005
DOI: 10.1128/mcb.25.15.6436-6453.2005
|View full text |Cite
|
Sign up to set email alerts
|

hnRNP K Binds a Core Polypyrimidine Element in the Eukaryotic Translation Initiation Factor 4E (eIF4E) Promoter, and Its Regulation of eIF4E Contributes to Neoplastic Transformation

Abstract: Translation initiation factor eukaryotic translation initiation factor 4E (eIF4E) plays a key role in regulation of cellular proliferation. Its effects on the m 7 GpppN mRNA cap are critical because overexpression of eIF4E transforms cells, and eIF4E function is rate-limiting for G 1 passage. Although we identified eIF4E as a c-Myc target, little else is known about its transcriptional regulation. Previously, we described an element at position ؊25 (TTACCCCCCCTT) that was critical for eIF4E promoter function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
99
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 113 publications
(131 reference statements)
4
99
1
3
Order By: Relevance
“…Interaction of A3B with several hnRNP proteins was also uniquely strong compared with other APOBEC3 proteins. It has been reported that hnRNP K and other hnRNP proteins participate in the transcriptional regulation of certain cellular and/or viral genes (Malik and Clements, 2004;Lynch et al, 2005;Ng et al, 2005;Yano et al, 2005). Whether one or more of the hnRNP proteins could mediate the suppression of CMV or SV40 promoter activities by A3B is an intriguing question.…”
Section: Discussionmentioning
confidence: 99%
“…Interaction of A3B with several hnRNP proteins was also uniquely strong compared with other APOBEC3 proteins. It has been reported that hnRNP K and other hnRNP proteins participate in the transcriptional regulation of certain cellular and/or viral genes (Malik and Clements, 2004;Lynch et al, 2005;Ng et al, 2005;Yano et al, 2005). Whether one or more of the hnRNP proteins could mediate the suppression of CMV or SV40 promoter activities by A3B is an intriguing question.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of hnRNP K is aberrantly increased in numerous cancers, including nasopharyngeal carcinoma (NPC; Pino et al, 2003;Carpenter et al, 2006;Hatakeyama et al, 2006;Roychoudhury and Chaudhuri, 2007;Chen et al, 2008). The tumorigenic activity of hnRNP K is conferred through its ability to increase proliferation (Lynch et al, 2005), clonogenic potential (Notari et al, 2006) and metastasis (Inoue et al, 2007). These effects may be due, at least in part, to the ability of hnRNP K to upregulate c-myc expression through the c-myc internal ribosome entry segment (IRES; Evans et al, 2003;Notari et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is active at the chromatin level, where it is present in a higher density at transcribed genes with respect to silent ones . Moreover, hnRNP K binds directly to the promoter region of the human c-myc gene (Michelotti et al, 1996) and promotes neoplastic transformation in an eIF4E-dependent manner (Lynch et al, 2005). In breast cancer cells, overexpression of hnRNP K enhances cell proliferation and anchorage-independent growth (Mandal et al, 2001), and in several states of enhanced cell proliferation, increased expression of this protein has also been found .…”
mentioning
confidence: 99%